Indonesian undergraduates' perspectives of translanguaging / Reni Kusumaningputri and Dewianti Khazanah - Reni, Kusumaningputri; Khazanah, Dewianti (Universiti Teknologi MARA, 2021)
The practice of translanguaging among English users is receiving growing attention as English is now perceived as a lingua franca, a global language. Most users, around 817 million (Bolton and Bacon-Shone, 2020) reside in Asia. This changing reality alters the sociolinguistic landscape of communication as English is spoken more by those who have diverse home languages. With an awareness that English is the property of its users, the response on how the practice of accommodating all linguistic resources they have needs examining. Although research concerning this issue has been increasing in countries where English is an additional language, how it is perceived by Indonesian undergraduates still receives less attention. In this current study, data was collected through a survey, and analyzed using descriptive statistics. Results indicate that translanguaging generally has a positive response in four different foci: as a practice, for English learning, for social uses, and in university context. Some implications on the policy are also discussed to respond to the findings